Analyzing the Jobless Recovery Phenomenon in the Nigerian Economy - Osiobe, Ejiro U.; Oseghe, Odezi M. (Journal of Applied Business and Economics, 2020)
This study examines jobless recovery and its effect on Nigeria’s economy. The underlying objective of this paper is to evaluate the trend between the increasing gross domestic product and the rate of unemployment in Nigeria. To empirically analyze the impact of the jobless recovery in the nation, we estimated a two-stage least square regression from 1986 to 2018, and our results support the view that the increasing real gross domestic product in the nation is associated with the country’s jobless recovery status.